The Role of Career Parents In Developing Social-Emotional Early Childhood - Ariq Nurjannah Irbah; Suyadi Suyadi; Ahmad Syafi'i Mufadzilah Riyadi; Ucik Hidayah Binsa (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
Career women are women who play a role in the household as well as play a role outside the home. This study discusses the role of career parents in developing social-emotional early childhood at Tunas Muda Magetan Kindergarten. This research aims to; find out information about the extent of parenting parents who have a career in developing social-emotional early childhood. This type of research used a qualitative research approach in the nature of a case study with a population of parents of early childhood at Poncol Magetan. The sampling technique is purposive sampling. Spread over 3 Kindergartens in Poncol District with a sample of 75 parents in Poncol. Data collection was in the form of questionnaires and interviews. Based on data analysis, it shows that there is a role for career parents in developing children's social-emotional development. From the study, it was found that role for career parent has an influence on the development of children's social abilities. This parenting style has the effect of giving children the opportunity and freedom to choose sincere actions and approaches, fostering attitudes and habits such as cooperation, mutual respect, tolerance and responsibility, because it can develop social and emotional development. Feel loved, valued, safe, competent and optimize their abilities.